2007
DOI: 10.1111/j.1551-2916.2007.01984.x
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Dynamic Study of Cementitious Calcium Silicate Hydrate (C–S–H) Gels

Abstract: In this article, we study the polymerization of silicic acids (Si(OH)4) in the presence of calcium ions by molecular dynamics simulations. We focus on the formation and structure of cementitious calcium silicate hydrate (C–S–H) gels. Our simulations confirm that, in accordance with experiments, a larger content of calcium ions slows down the polymerization of the cementitious silicate chains and prevents them from forming rings and three‐dimensional structures. Furthermore, by an analysis of the connectivity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
76
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(93 citation statements)
references
References 33 publications
15
76
1
1
Order By: Relevance
“…This means that the three peaks found for C-S-H by HRTG do not correspond to polymorphs of this phase, but yes to different processes of decomposition. This interpretation agrees with the models proposed for C-S-H, where water can be found between the mineral layers or in the form of OH -radicals, linked to tetrahedral silicon or to octahedral calcium [18][19][20][21][22]. Due to what was explained in the last paragraph, it was decided that we would add the mass loss of the three peaks ( Fig.…”
Section: Mineralogysupporting
confidence: 62%
“…This means that the three peaks found for C-S-H by HRTG do not correspond to polymorphs of this phase, but yes to different processes of decomposition. This interpretation agrees with the models proposed for C-S-H, where water can be found between the mineral layers or in the form of OH -radicals, linked to tetrahedral silicon or to octahedral calcium [18][19][20][21][22]. Due to what was explained in the last paragraph, it was decided that we would add the mass loss of the three peaks ( Fig.…”
Section: Mineralogysupporting
confidence: 62%
“…Second, the globule disk radius R increases in samples with additives of PCE23-2 and PCE102-6. This means that when adding PCE23-2 and PCE102-6, the microstructure of CÀSÀH becomes more like the continuous extension of branched or interconnected multi-lamellar sheets, as in the models proposed by Dolado et al [17,18] and McDonald et al [19]. In addition, by fitting the SAXS data with IðQ Þ ¼ C p  Q À4 in the range of 0.23 Å À1 < Q < 0.29 Å À1 , where the contribution from S(Q) is negligible, we found that the Porod constant C p (not shown), which is proportional to the total surface area per volume, has the trend: CÀSÀH > CÀSÀH/PCE102-2 > CÀSÀH/PCE23-6 > CÀSÀH/PCE23-2 > CÀSÀH/PCE102-6.…”
Section: Resultsmentioning
confidence: 83%
“…Varios trabajos de simulación ya han sido descritos en la literatura, pero o bien han prestado atención a la justificación computacional de los cristales de tobermorita y jennita como modelos estructurales (13)(14) o bien han determinado diferentes propiedades dinámicas y estructurales asumiendo estos modelos cristalinos (15)(16)(17)(18)(19). Desafortunadamente, todos ellos han centrado su atención en el orden a corto alcance del gel C-S-H sin tener en cuenta la conexión a escala coloidal.…”
Section: Introductionunclassified
“…Some attempts have been already made, but either they have paid attention to the computational justification of the jennite and tobermorite crystals as appropriate structural models (13)(14) or they have determined different structural and dynamical properties by assuming these crystalline models (15)(16)(17)(18)(19). Unfortunately, all of them have centred their attention to the short-ordering of C-S-H, being the linkage with the colloidal scale not covered.…”
Section: Procedimiento De Simulación: Formación De Estructuras Ld Y Hmentioning
confidence: 99%